PERSEPSI IBU HAMIL TRIMESTER III TENTANG DUKUNGAN SUAMI MENJELANG PROSES PERSALINAN DI PUSKESMAS KRETEK - Iin Setiyani; Reni Merta Kusuma (Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Social support, especially from the husband is a major factor that affects the occurrence of anxiety in the period of pregnancy to childbirth. Anxiety experienced by pregnant women can be prevented by the support of the closest people like mother or mother-in-law, especially the husband because the presence of the closest people will bring peace to the mother’s prespective during pregnancy. Objevtive:The purpose of this study was determine the perception of pregnant women in their third trimester about the support from the husband before the delivery process at Kretek Bantul Public Health Center. Methods: This research method was a descriptive research type. The samples used were 35 pregnant women in their third pregnancy at Puskesmas Kretek by using total sampling. Primary data collection used closed questionnaire then analyzed by using frequency distribution and percentage. Results: The results of the study showed that the perception of pregnant women about the majority of informational support supported as many as 25 respondents (71.4%), the support of majority assessment supported as many as 27 respondents (77.1%), majority support instrumental support as many as 24 respondents (68.6%), and majority emotional support does not support as many as 22 respondents (62.9%). Conclusion: The conclusion of this research is perception of pregnant mother in the third trimester about support from husband before childbirth majority support are 29 respondents (82,9%). Keywords: Husband, social support, pregnancy